2022
DOI: 10.3389/fimmu.2022.809872
|View full text |Cite
|
Sign up to set email alerts
|

A Signature of N6-methyladenosine Regulator-Related Genes Predicts Prognoses and Immune Responses for Head and Neck Squamous Cell Carcinoma

Abstract: This study aimed to construct a signature of N6-methyladenosine (m6A) regulator-related genes that could be used for the prognosis of head and neck squamous cell carcinoma (HNSCC) and to clarify the molecular and immune characteristics and benefits of immune checkpoint inhibitor (ICI) therapy using the prognostic signature to define the subgroups of HNSCC. This study showed that eighteen m6A regulators were abnormally expressed in the Cancer Genome Atlas (TCGA) HNSCC tissues compared with those in normal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…At the same time, we also predicted the immune response and score using Tumor Immune Dysfunction and Exclusion (TIDE) online tools (http://tide.dfci.harvard.edu) and the IMvigor210CoreBiologies R package. 26 Correlation analysis between risk scores and expression level of immune checkpoint was performed using the ggcorrplot R package. 27…”
Section: Prediction Of Immunotherapy/ Chemotherapymentioning
confidence: 99%
“…At the same time, we also predicted the immune response and score using Tumor Immune Dysfunction and Exclusion (TIDE) online tools (http://tide.dfci.harvard.edu) and the IMvigor210CoreBiologies R package. 26 Correlation analysis between risk scores and expression level of immune checkpoint was performed using the ggcorrplot R package. 27…”
Section: Prediction Of Immunotherapy/ Chemotherapymentioning
confidence: 99%
“…Furthermore, m 6 A modifications have essential roles during the generation of immune responses ( 112 ). A previous study indicated that, depending on m 6 A regulation-related genes, a prognostic marker may effectively determine the prognosis of HNSCC ( 113 ). This prognostic marker was associated with immune cell infiltration in HNSCC ( 113 ).…”
Section: Immunomodulatory Potential Of M 6 a Modif...mentioning
confidence: 99%
“…A previous study indicated that, depending on m 6 A regulation-related genes, a prognostic marker may effectively determine the prognosis of HNSCC ( 113 ). This prognostic marker was associated with immune cell infiltration in HNSCC ( 113 ). A recent study suggested that METTL3 expression was increased in OSCC and inhibited CD8 + T-cell activation ( 106 ).…”
Section: Immunomodulatory Potential Of M 6 a Modif...mentioning
confidence: 99%
“…Second, we also explored the expression of N6-methyladenine (m6A) related genes between the two groups. The gene related to N6-methyladenine (m6A) was obtained from the previous literature 14 . The "ggpubr" and "ggplot2" R packages were used to perform this study.…”
Section: Gene Set Enrichment Analysesmentioning
confidence: 99%